2019
DOI: 10.1111/jnu.12474
|View full text |Cite
|
Sign up to set email alerts
|

Role of Career Satisfaction in Basic Psychological Needs Satisfaction and Career Commitment of Nurses in Nigeria: A Self‐Determination Theory Perspective

Abstract: Purpose The purpose of this study was to test how basic psychological needs satisfaction contributes to career commitment through career satisfaction among nurses. Background There is an increasing rate of turnover among nurses and a general shortage of nurses in many countries. This has made it necessary for researchers to focus on the career satisfaction of nurses and their commitment to their careers. Design and Methods A cross‐sectional design was employed in a survey of 233 nurses in public hospitals in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
4
18
0
Order By: Relevance
“…Supplementary analyses of non-hypothesized possibilities suggested that career satisfaction plays a role in predicting career commitment. This implies that employees who are more satisfied with their careers are more likely to be committed to their careers, corroborating the findings of Onyishi et al (2019).…”
Section: Discussionsupporting
confidence: 80%
“…Supplementary analyses of non-hypothesized possibilities suggested that career satisfaction plays a role in predicting career commitment. This implies that employees who are more satisfied with their careers are more likely to be committed to their careers, corroborating the findings of Onyishi et al (2019).…”
Section: Discussionsupporting
confidence: 80%
“…Heinen et al (2013) reported that nurses with a positive working environment perception had 30% lower ITL the profession. Onyishi, Enwereuzor, Ogbonna, Ugwu, and Amazue (2019) found that nurses’ career satisfaction was positively correlated with career commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Career satisfaction is an individual’s evaluation of an organizational/workplace factors (e.g., advancement, development, and income) relative to their own goals, expectations, and accomplishments [ 39 ]. It is an important construct in career success and commitment [ 40 ]. In academia, one key aspect of faculty career satisfaction is the nature of the work itself as it relates to teaching, research, and service obligations [ 41 ].…”
Section: Introductionmentioning
confidence: 99%